Hubungan Inflasi, Suku Bunga, Produk Domestik Bruto, Nilai Tukar, Jumlah Uang Beredar, dan Indeks Harga Saham Gabungan (IHSG) Periode 2005-2011 - Nofiatin, Ike (Universitas Brawijaya, Indonesia, 2013)
This study aims to determine the co-integration relationship and causality relationship betweenmacroeconomic variables and IHSG in BEI (Indonesia Stock Exchange). Study's sample consists of 84 organizations which are taken from January 2005 to December 2011. The analysis technique is Vector Autoregression (VAR). The analysis result shows that there is a co-integration relationship between inflation, interest rates, exchange rates, and stock index, but there is no similarity between the movement of theGDP, money supply, and stock index. In addition, there were no two-way causality between macroeconomic variables and stock index. The analysis shows that there are some one-way causality relationships between macroeconomic variables and stock index during the period of the study.